Guidelines for patrolling community fish refuge systems - Ou, Phichong; Sean, Vichet; Sun, Vathanak; Chhy, Savry; Lim, Nget; Mam, Sovannary; Phin, Phearum; Eng, Kimleng; Samon, Channa (WorldFish, 2024)
Considering that patrols in community fish refuge ponds are an important part of increasing natural fish stocks and protecting fish species to ensure the sustainability of fisheries resources, the Fisheries Administration, in collaboration with WorldFish and the Sustainable Aquaculture and Community Fish Refuge Management project, has developed a set of guidline. Guidelines for patrolling community fish refuge systems for technical assistance in managing CFR pond systems. This document describes the threats to the CFR pond, the purpose of the patrol, the responsibilities of the patrol team, the location and time of the patrol, the steps of the CFR pond patrol (understanding of fisheries laws and community bylaw, measures during the patrol); monitor and evaluate.